2016
DOI: 10.1103/physreve.94.012118
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion and dynamics of fluorescence recovery after photobleaching in the random-comb model

Abstract: We address the problem of diffusion on a comb whose teeth display a varying length. Specifically, the length ℓ of each tooth is drawn from a probability distribution displaying the large-ℓ behaviorOur method is based on the mean-field description provided by the well-tested CTRW approach for the random comb model, and the obtained analytical result for the diffusion coefficient is confirmed by numerical simulations. We subsequently incorporate retardation effects arising from binding/unbinding kinetics into ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Here, h(u, t) is the so-called subordination function. The latter is the PDF, which subordinates the process governed by Equation (21) to the process governed by Equation (13). By the Laplace transform of Equation ( 23), and by using the subordination function h(u, s) = 1 sη(s) e −u/η(s) , (…”
Section: One-dimensional Diffusion-advection Equation With Stochastic Resettingmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, h(u, t) is the so-called subordination function. The latter is the PDF, which subordinates the process governed by Equation (21) to the process governed by Equation (13). By the Laplace transform of Equation ( 23), and by using the subordination function h(u, s) = 1 sη(s) e −u/η(s) , (…”
Section: One-dimensional Diffusion-advection Equation With Stochastic Resettingmentioning
confidence: 99%
“…Different generalizations of the comb geometry have been considered. For example, various diffusion processes have been considered in a comb with a finite finger length [4][5][6], diffusion on cylindrical [7,8] and circular combs [9][10][11], more complex branched structures [12], random comb models [13], and a comb with ramified teeth [14], as well as the problem of first encounters for two workers [15]. Diffusion processes in fractal mesh and grid structures have been considered as well: In this case, anomalous diffusion of a particle is affected by the fractal structure of the infinite numbers of backbones and fingers [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we consider a diffusion process on the times t > h. In this case, there is a simple relation between these PDFs P (x, y = 0, t) ∼ hρ(x, t), which reduces to the equality at the asymptotically large time scale, t ≫ h. As it follows from Ref. [15], this relation should be also true for random finger's length with the finite mean length of the order of h.…”
mentioning
confidence: 95%
“…It has been shown in experimental and numerical studies that the transport of inert particles along dendrite structure of neurons corresponds to anomalous diffusion (namely subdiffusion), when the temporal behavior of the MSD is of the power law t γ , where the transport exponent 0 < γ < 1 depends on the geometry and density of the dendritic spines [9][10][11]. Dendritic spines are the basic functional units in pre-and post synaptic activity of neurons [12], and further studies have shown that the comb model can be used to describe the movement and binding dynamics of particles, including reaction transport of Ca 2+ ions inside the spines [13][14][15]. A comb model has been suggested as a simplified toy model, which reflects this property of anomalous diffusion, resulted from the geometry, which mimics geometry of spiny dendrites, such that the backbone is the dendrite and the fingers are the spines, see Fig.…”
mentioning
confidence: 99%